2012
DOI: 10.1016/j.jelectrocard.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic reprogramming of the left ventricle: translation to the ECG

Abstract: Hypertrophic growth of the heart occurs in many clinical scenarios, and it confers substantially increased risk of untoward sequelae. Among them, transition to ventricular dilation, wall thinning, contractile dysfunction, and a clinical syndrome of heart failure is paramount. Left ventricular hypertrophy (LVH) is typically diagnosed by either electrocardiography or echocardiography. However, these two means of assessing hypertrophic transformation of the left ventricle can sometimes disagree. At one level, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Whereas the great majority of studies – again, exclusively in rodents to date – demonstrate that the load-induced growth response can be inhibited without untoward effects, there are examples where hypertrophy elicited by a specific signaling cascade appears to be required 135-137 . Also, ventricular mass alone may not provide the full picture of the myriad remodeling events involved in heart growth 138 . Therefore, further work is required to determine whether accompanying alterations (e.g.…”
Section: A Note Of Cautionmentioning
confidence: 99%
“…Whereas the great majority of studies – again, exclusively in rodents to date – demonstrate that the load-induced growth response can be inhibited without untoward effects, there are examples where hypertrophy elicited by a specific signaling cascade appears to be required 135-137 . Also, ventricular mass alone may not provide the full picture of the myriad remodeling events involved in heart growth 138 . Therefore, further work is required to determine whether accompanying alterations (e.g.…”
Section: A Note Of Cautionmentioning
confidence: 99%
“… 1 , 6 Myocardial hypertrophy can lead to both prolonged LV tissue repolarization and slowing of conduction velocity. 7 , 8 Slowing of conduction velocity through the cardiac ventricles is marked by QRS interval widening. 8 Conduction slowing in the setting of cardiac hypertrophy may include impaired coronary vasodilator reserve, decreased capillary density, altered gap junction expression, increased individual cardiac myocyte cell diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the traditional model assuming that increased anatomical LVM leads to increased QRS voltage was challenged . It was suggested that this would be the case only in the presence of “ideal hypertrophy” (diffuse and symmetrical, with unaltered sequence and velocity of electrical activation), whereas “true” ventricular hypertrophy is a complex rebuilding of the myocardium including structural, bioelectrical, and biochemical changes, all interacting and leading to adverse clinical outcomes …”
Section: Discussionmentioning
confidence: 99%
“…4,34 It was suggested that this would be the case only in the presence of "ideal hypertrophy" (diffuse and symmetrical, with unaltered sequence and velocity of electrical activation), 35 whereas "true" ventricular hypertrophy is a complex rebuilding of the myocardium including structural, bioelectrical, and biochemical changes, all interacting and leading to adverse clinical outcomes. 34,36 There are few studies to date addressing the effect of altered electrical properties of the hypertrophied myocardium on QRS characteristics in LVH patients. In a computer model-study, Bacharova et al demonstrated that a gradual reduction in intercellular coupling in the LV myocardium caused a decrease in the QRS magnitude despite increased LVM.…”
Section: Discussionmentioning
confidence: 99%